2015
DOI: 10.1111/btp.12198
|View full text |Cite
|
Sign up to set email alerts
|

Carry‐over Effects of Size at Metamorphosis in Red‐eyed Treefrogs: Higher Survival but Slower Growth of Larger Metamorphs

Abstract: Most animals have complex life histories, composed of a series of ecologically distinct stages, and the transitions between stages are often plastic. Anurans are models for research on complex life cycles. Many species exhibit plastic timing of and size at metamorphosis, due to both environmental constraints on larval growth and development and adaptive plastic responses to environmental variation. Models predicting optimal timing of metamorphosis balance cost/benefit ratios across stages, assuming that size a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 61 publications
2
35
0
Order By: Relevance
“…, Tarvin et al. ), we predict a subsequent reduction in individual fitness (Fig. ; Rowe and Ludwig , Ludwig and Rowe ).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…, Tarvin et al. ), we predict a subsequent reduction in individual fitness (Fig. ; Rowe and Ludwig , Ludwig and Rowe ).…”
Section: Discussionmentioning
confidence: 51%
“…, Tarvin et al. , Van Allen and Rudolf ). However, carry‐over effects may represent an important alternate prey response mechanism as they are driven by ontogenetic exposure regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Tarvin et al . () found that larger A. callidryas froglets from low larval densities lost significant mass for a period of 1–3 weeks. This mass loss can be explained by the marked delay in the onset of feeding that we found for large individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Such measures accurately reflect froglet intake because small and large froglets do not preferentially select small or large leafhoppers or fruit flies when ad libitum food is provided following our methods (Tarvin et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation